FLAIR-hyperintense lesions in anti-MOG-associated encephalitis with seizures overlaying anti-N-methyl-D-aspartate receptor encephalitis: a case report and literature review - Yang, Jia-Xin; Yang, Miao-Miao; Han, Yu-Juan; Gao, Cai-Hong; Cao, Jie (Frontiers in Immunology, 2023)
Background：FLAIR-hyperintense Lesions in Anti-MOG-associated Encephalitis With Seizures (FLAMES) have been gradually identified in recent years. However, this rare MOG antibody disease coexists with anti-N-methyl-D-aspartate receptor encephalitis (anti-NMDARe) with unknown clinical features and prognosis. Methods：We report a new case. In addition, the similar cases in the literature were systematically reviewed. To study the clinical presentation, MRI, EGG abnormalities, treatment and prognosis of patients with this rare overlap syndrome. Results：12 patients were analyzed in this study. Epilepsy (12/12), headache (11/12), and fever (10/12) were the most common clinical manifestations of MOG cerebral cortical encephalitis (CCE) overlay with anti-NMDARe. Intracranial pressure elevated (median 262.5 mmH2O, range 150-380 mmH2O), cerebrospinal fluid (CSF) leukocytes elevated, (median 128*106/L, range 1-610*106/L), protein level elevated, median 0.48 g/L. CSF anti-NMDAR antibody titer median 1:10 (1:1-1:32) and serum MOG antibody titer median 1:32 (1:10-1:1024). 7 cases showed unilateral cortical FLAIR hyperintense. 5 cases (42%) showed bilateral cortical FLAIR hyperintense, including 4 cases with bilateral medial frontal lobes. 5/12 patients showed lesions at other sites (e.g., brainstem, corpus callosum, frontal orbital gyrus, etc.) before or after cortical encephalitis. EEG showed slow waves in 4 cases, spike-slow waves in 2 cases, epileptiform pattern in 1 case, and normal in 2 cases. Relapses were a median of 2 times. At a mean follow-up time of 18.5 months, only one patient had residual visual impairment and the others had a good prognosis. Conclusion: MOG-ab-positive CCE alone is difficult to distinguish from overlap syndrome by clinical features, etc. However, MOG-ab-positive CCE patients with bilateral medial frontal lobe may suggest overlap syndrome.